Correlation analysis of geomagnetic parameters during geomagnetic storm / Nur Farhana Zaihan and Noor Hafizah Abdul Aziz - Zaihan, Nur Farhana; Abdul Aziz, Noor Hafizah
The Sun is the most important driver of space weather phenomenon. Energetic particles thrown out from the Sun interact with the Earth's magnetic field producing geomagnetic disturbances (storms) and increased ionization in the ionosphere. Geomagnetic storms have seriously effects on the electric power systems. This paper presents the analysis of geomagnetic data during three geomagnetic storm events of 9th April 2006, 14,h April 2006 and 14"" December 2006. The data were taken from MAGDAS unit at Ashibctsu Stataion, Japan which supplied by Space Environment Research Center (SERC) Kyushu Universiti, Japan. The analysis shows higher variations detected on geomagnetic parameter (II parameter) on the day of geomagnetic storm and long lasting until two days after the event.